THE BAUER SCARP RIDGE JUMP: A COMPLEX TECTONIC SEQUENCE REVEALED IN SATELLITE ALTIMETRY - Goff J.A.; Cochran J.R. (My University, 1996)
We investigate here the ridge jump that led to abandonment of the Galapagos Rise and formation of the Bauer scarp during the initiation of the present day configuration of the East Pacific Rise since the lower Miocene. We use recently available high resolution satellite-derived gravity data to investigate in detail the tectonic structure of the eastern Pacific from the Equator to 20oS. With this data, we identify fracture zones, abandoned spreading ridges, scarps, and other seafloor features that provide evidence for discerning tectonic history.Based on our structural interpretation of the satellite-derived gravity field, we make the following conclusions: (1) The Galapagos Rise spreading center appears to have originated by opening of the Marquesas/Mendana transform complex as a result of the change in spreading direction following breakup of the Farallon Plate. (2) The Galapagos Rise was not the sole locus of spreading following plate reorganization at # 20 Ma through to the initiation of the Bauer scarp at # 8 Ma, as had been previously hypothesized. Rather, it and a second western spreading axis were likely active concurrently, forming a counterclockwise-rotating Bauer Microplate at a much earlier stage than thought previously. (3) The Bauer scarps are pseudofaults associated with northward rift propagation. Propagation proceeded in several stages. A first propagator emanating from the Garrett transform complex stalled at the future location of the Wilkes transform creating an area of complex morphology near its northern tip. A second propagator, also emanating from the Garrett complex followed in the first's wake and broke through the complex region. At this point the propagation proceeded very rapidly to the northern end of the Bauer Microplate (the Gallego fracture zone, later to become the Yaquina transform fault). Ridge propagation continued north in two more stages, creating the Gofar and Quebrada transforms at the terminus of each stage.
Keywords: EAST PACIFIC RISE; SPREADING CENTERS; GRAVITY SURVEYS; SATELLITE METHODS